2017
DOI: 10.1002/celc.201700917
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Production by Direct Lignin Electrolysis at Intermediate Temperatures

Abstract: Hydrogen is produced conventionally by electrolyzing water or water vapor at onset voltages greater than 1 V, providing motivation for the development of more efficient electrolysis processes for a hydrogen economy. Numerous attempts have been made to use ethanol as a fuel for hydrogen production because this process reduces the electrolysis onset voltage significantly. However, ethanol feedstock from lignocellulose requires greater amounts of energy and results in higher production costs compared to those usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 28 publications
(34 reference statements)
1
31
0
Order By: Relevance
“…52,360,375,381,382 At neutral conditions, biological catalysts can be utilized, but the systems enabling a sustainable and durable production of H2 at a low electrical energy input are those based on abiotic electrocatalysts. The first electrolysis cells fuelled by the lignin was reported in 2017 by Hibino et al 381 The study was describing the direct lignin electrolysis at an onset voltage of ca. 0.25 V (note that water electrolysis cannot start below 1.4 V), with high current efficiencies of approximately 100% for H2 production at the cathode and approximately 85% for CO2 production at the anode.…”
Section: Biomass-fuelled Electrolysis Cells For Simultaneous Production Of H2 Fuel and Chemicalsmentioning
confidence: 99%
“…52,360,375,381,382 At neutral conditions, biological catalysts can be utilized, but the systems enabling a sustainable and durable production of H2 at a low electrical energy input are those based on abiotic electrocatalysts. The first electrolysis cells fuelled by the lignin was reported in 2017 by Hibino et al 381 The study was describing the direct lignin electrolysis at an onset voltage of ca. 0.25 V (note that water electrolysis cannot start below 1.4 V), with high current efficiencies of approximately 100% for H2 production at the cathode and approximately 85% for CO2 production at the anode.…”
Section: Biomass-fuelled Electrolysis Cells For Simultaneous Production Of H2 Fuel and Chemicalsmentioning
confidence: 99%
“…The impedance spectra suggest that the I-V characteristics reflect the order of polarization resistance during electrolysis. The relatively large polarization resistance of lignin for electrolysis has been reported previously 40 . Note that lignin in this experiment is referred to as a Klason lignin, which is obtained as a residue from the hydrolysis of lignocellulosic materials and is partially altered using concentrated sulfuric acid at elevated temperature and high pressure 41 .…”
Section: Resultsmentioning
confidence: 56%
“…[85] Nong et al also demonstrated that electrolysiso fB Lu sing ac ationic electrolytic reactor equipped with ac ation-exchange membrane can result in the recovery of 80.4 %N aOH and 76 %b iomass residue while cogenerating 0.82 go fhydrogen gas. [158] More recently,H ibino et al [159] and Caravaca et al [160] both studied hydrogen production assisted by lignin electrolysis in a polymer electrolyte membrane reactor at PtFe/C and Pt-Ru anodes, respectively.Inthe study by Hibino et al an onset voltage of 0.25 Vand temperature of 100-200 8Cr esulted in 100 % current efficiency for hydrogen production.T emperature was found to enhance I-V curve (current vs. cell-voltage curve) characteristics due to ad ecrease in ohmic and polarization resistances. Further improvement of the current density was achieved at 150 8Cv ia the use of at hinner electrolyte membrane and the addition of H 3 PO 4 -impregnated lignin.…”
Section: Electrochemical Degradation Of Lignin For Hydrogen Co-producmentioning
confidence: 99%